2013
DOI: 10.1002/anie.201301362
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Screening for Terpene‐Synthase‐Cyclization Activity and Directed Evolution of a Terpene Synthase

Abstract: A synthetic substrate enables a new colorimetric screen for terpene synthase cyclization activity, facilitating the engineering of these enzymes. Using directed evolution, the thermostability of the sesquiterpene synthase BcBOT2 was increased without the loss of other properties. The technique also enabled rapid optimization of conditions for expression and stabilization in lysate of another terpene synthase, SSCG_02150.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 44 publications
2
75
0
1
Order By: Relevance
“…Since switching the BIS promoter from GAL10 to GAL1 increased bisabolene production 2-fold (comparing the pESC strain to the pRS strain), it seemed a reasonable assumption that BIS is a limiting factor in the yeast bisabolene biosynthetic pathway. This is in agreement with unpublished data on bisabolene production in yeast together with findings that, due to their relatively slow kinetics, terpene synthases are commonly found to be the limiting enzymes in terpene biosynthetic pathways (21)(22)(23).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Since switching the BIS promoter from GAL10 to GAL1 increased bisabolene production 2-fold (comparing the pESC strain to the pRS strain), it seemed a reasonable assumption that BIS is a limiting factor in the yeast bisabolene biosynthetic pathway. This is in agreement with unpublished data on bisabolene production in yeast together with findings that, due to their relatively slow kinetics, terpene synthases are commonly found to be the limiting enzymes in terpene biosynthetic pathways (21)(22)(23).…”
Section: Resultssupporting
confidence: 92%
“…There is, however, a scarcity of tools available for high-throughput screening or selection of improved strains. An FPP analog which releases methanol upon enzyme-mediated cyclization has been used as a synthetic substrate to successfully increase the thermostability of a sesquiterpene synthase (22). This approach reduces processing time for screening a mutant library but still requires lysis and assay of each mutant on an individual basis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, metabolic engineering of terpene biosynthetic pathways has received a formidable interest [3] for the generation of valuable polycyclic and multichiral natural products that would be challenging to synthesize by traditional chemical methodologies [4]. Only recently the potential of terpene cyclases to generate complexity beyond nature's current capabilities started to become realized [5][6][7][8]. Harnessing the catalytic machineries of terpene synthases for novel chemistries could in principle be based on either of the two natural mechanisms for the generation of a reactive carbocationic species prone to further chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, Lauchli et al [22] demonstrated that TPS could be a target for directed evolution by using a surrogate substrate for FPP. They synthesized vinyl ether containing isoprenyl diphosphate, which is similar to FPP.…”
Section: Introductionmentioning
confidence: 99%